Gender and second-temple Judaism - Ehrensperger, Kathy; Sheinfeld, Shayna (Lexington Books/Fortress Academic, 2020)
Introduction: Gender and Second Temple Judaism: Challenges and PossibilitiesShayna Sheinfeld Chapter 1"The Brooten Phenomenon": Moving Women from the Margins in Second-Temple and New Testament ScholarshipSara Parks Chapter 2Women Itinerants, Jesus of Nazareth, and Historical-Critical Approaches: Reevaluating the Con-sensusAmy-Jill Levine Chapter 3Paul, the Man: Enigmatic ImagesKathy Ehrensperger Chapter 4From Pain to Redemption: 1 Timothy 2:15 in its Jewish ContextSarah E.G. Fein Chapter 5Traversing the Boundaries of Gender: Rebekah's Usurpation of the Patriarchal Role in the Book of JubileesChontel Syfox Chapter 6The Reinforcement of Patriarchy and the (De)Construction of Gender Roles in Jubilees' Recep-tion of the Jacob-Esau-NarrativeDaniel Vorpahl Chapter 7Women and Gender in the Gospel of JohnAdele Reinhartz Chapter 8The Framing of Female Knowledge in the Prologue of the Sibylline OraclesFrancis Borchardt Chapter 9Female Authorship in Jewish Antiquity?Gerbern Oegema Chapter 10Pheroras' Wife: A Pharisee WomanTal Ilan Chapter 11Cross-dressing Zealots in Josephus's War AccountGabriella Gelardini Chapter 12Female Officiants in Second Temple Judaism Angela Standhartinger